71.5k views
0 votes
6. – 4y + 8x = 32 for y

User DEKKER
by
5.2k points

2 Answers

4 votes

Answer:

Explanation:

-4y + 8x = 32

⇔ -4y = 32 - 8x

⇔ y =
(32 - 8x)/(-4)

⇔ y =
(8*(4-x))/(-4)

⇔ y = -2*(4-x)

⇔ y = -8 + 2x

⇔ y = 2x -8

User Ahmadalibaloch
by
4.9k points
6 votes

Answer:

The answer is: y=2x−8

Explanation:

Step 1: Add -8x to both sides.

8x−4y+−8x=32+−8x

−4y=−8x+32

Step 2: Divide both sides by -4.

−4y−4=−8x+32−4

y=2x−8

User Gpa
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.